EFEKTIVITAS KOMUNIKASI PEMBELAJARAN DARING PADA SISWA/I SMK LP3ISTANA - Jana Sandra; Novfitri Landong Namora Sihombing; Amiruddin Qadaar; Supratiningsih (CV ODIS, 2022)
Pandemic Covid 19, changing lifestyles and daily behavioral conditions, including learning and working Online Learning one of the learning strategies in the current condition of Availability of Learning Resources and supporting facilities (network/readiness of digital materials, and others. This research was conducted to describe the implementation of online learning and communication conducted by students with teachers during the online learning process conducted at SMK LP3ISTANA JAKARTA. The type of research used by researchers using post positivistic paradigms, which are deductive, research that starts from theory but is not included for hypothesis testing, Quantitative and qualitative observation research techniques, the research includes various data collection techniques not only quantitative approaches but also qualitative, the quality of validity and reliability research, whether the research can really precisely measure what is measured (validity) and if the research is repeated will produce the same findings (rehabilitation). The results of the study are Cronbach alpha (?) count obtained a value of 0.663 at an interval of 0.6??<0.7 then it can be concluded that communication at the time of online learning has been done quite well.